2019
DOI: 10.1103/physrevlett.122.204804
|View full text |Cite
|
Sign up to set email alerts
|

Phase Space Dynamics of a Plasma Wakefield Dechirper for Energy Spread Reduction

Abstract: Plasma-based accelerators have made impressive progress in recent years. However, the beam energy spread obtained in these accelerators is still at ∼ 1% level, nearly one order of magnitude larger than what is needed for challenging applications like coherent light sources or colliders. In plasma accelerators, the beam energy spread is mainly dominated by its energy chirp (longitudinally correlated energy spread). Here we demonstrate that when an initially chirped electron beam from a linac with a proper curre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…The peak energy of this spike is 0.2 GeV with a rms energy spread of ∼3%. The bunch has a large negative chirp, which increases the projected energy spread; however, the slice energy spread remains as low as ∼0.5% throughout the whole bunch, and it has been demonstrated that the negative chirp of the bunch can be removed by a plasma dechirper [46][47][48] so that the projected energy spread of the bunch can be reduced to be comparable to the slice energy spread. In another simulation where the length of the plasma is 2 cm, the peak energy of the beam exceeds 1 GeV.…”
Section: Full-scale Simulationmentioning
confidence: 99%
“…The peak energy of this spike is 0.2 GeV with a rms energy spread of ∼3%. The bunch has a large negative chirp, which increases the projected energy spread; however, the slice energy spread remains as low as ∼0.5% throughout the whole bunch, and it has been demonstrated that the negative chirp of the bunch can be removed by a plasma dechirper [46][47][48] so that the projected energy spread of the bunch can be reduced to be comparable to the slice energy spread. In another simulation where the length of the plasma is 2 cm, the peak energy of the beam exceeds 1 GeV.…”
Section: Full-scale Simulationmentioning
confidence: 99%
“…4, the total energy spread has been reduced by a factor of ∼ 20 down to 0.12% with respect to a case with no chirp compensation. This corresponds to a dechirping strength of 1.1 GeV/µm/m, orders of magnitude higher than in other schemes [34][35][36][37][38]. The slice energy spread has also been reduced to just 2.8×10 −4 , when considering 0.1 µm slices.…”
mentioning
confidence: 79%
“…The presented scheme therefore offers a path towards beams with ultra-low energy spread (∼ 10 −4 ) while reducing the sensitivity to issues such as the timing jitter for external injection and the hosing instability. The dechirping strength offered by this concept is orders of magnitude higher than in other proposals [34][35][36][37][38], and allows for dechirping while further accelerating the beam. The concept is ideally suited for PBAs with weakly or linearly beam-loaded wakefields where the beam develops a negative chirp before the magnetic chicane.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Major efforts have therefore been dedicated towards this objective, including the development of controlled injection techniques [23][24][25][26][27] as well as concepts for mitigating the correlated energy spread arising from the steep slope of the accelerating fields. These include beam loading the wake [28][29][30] , either by the accelerated bunch itself 31 or the injection of a secondary one 32 , the use of modulated 33 or tailored 34 plasma profiles, the insertion of a magnetic chicane in a multistage PBA 35 , or taking advantage of the beam-induced wakefields [36][37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%